NOVEL TYPE OF PHOSPHORUS-HUMIC FERTILIZERS BASED ON LOW-GRADE KARAKALPAK PHOSPHORITES - Temirov Uktam, Namazov Shafoat, Kanoatov Khayrullo Usanbayev Najimuddin, Abduazizov Nabijon, Nurmurodov Tulqin, Azimova Durdona (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
In this article, composts are prepared based on manure and phosphorite at mass manure ratios: phosphorite (from 100 : 5 to 100 : 30). Water was added to the prepared mixture based on the calculation to achieve 70% moisture content. It was determined the kinetics and degree of organic part transformation of manure into humic substances and indigestible phosphorus forms into a form assimilable for plants in slime phosphorite.